The Effect Of Education And Income On Household Consumption Patterns In Kelurahan Seberang Padang - Burhanuddin; Azzahra Nikmatul Ilmi; Wulandari Pryangan; Nita Hasnita; Wa Ode Irma Sari (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
This study examines the effect of education and income on household consumption patterns in Kelurahan Seberang Padang, motivated by preliminary findings showing that most households still prioritize basic needs over spending on education, health, and savings. Variations in consumption behavior were also observed, largely influenced by the education level of the household head and monthly income. Using a quantitative approach with survey techniques, the research involved 75 purposively selected respondents. Data were analyzed using multiple linear regression to measure the simultaneous and partial effects of education and income on consumption patterns. The results show that education has a positive and significant influence on consumption allocation (β = 0.28, p < 0.05), while income also significantly affects consumption behavior (β = 0.41, p < 0.01). Together, these variables explain 34% of the variation in household consumption patterns (R² = 0.34). The findings indicate that higher education and income levels encourage households to allocate a greater proportion of expenditure toward quality-of-life needs such as health, education, and savings. In conclusion, education and income play important roles in shaping consumption behavior in the community. The study implies the need for strengthening local programs related to education improvement and financial literacy to foster more balanced, productive, and sustainable household consumption patterns.